A healthy dietary pattern associates with a lower risk of a first clinical diagnosis of central nervous system demyelination - Ausimmune Investigator Group; Black, LJ; Rowley, C; Sherriff, J; Pereira, G; Ponsonby, A-L; Lucas, RM (SAGE Publications, 2018)
Background: The evidence associating diet and risk of multiple sclerosis is inconclusive.